The Revitalization of Education Character in The Pandemic Covid-19 Era - Senata Adi Prasetia; Siti Firqo Najiyah (State Islamic Institute of Madura, 2021)
The character education during the Covid-19 pandemic has found significance. A survey conducted by Balitbang of East Java Province on community compliance with the use of masks and physical distance in the prevention of Covid-19 in Surabaya shows that 10.8% of the level of community compliance with the use of masks is very low, and 25.45% of the level of community compliance with physical distances is also very low. The survey above indicates that so far the character education taught in educational institutions has not made an impact and remains in people's behavior. Therefore the revitalization of character education during the Covid-19 pandemic is a must. This study aims to explore three main issues: 1) Covid-19 and online learning; 2) character education problems in online learning; 3) and revitalizing character education during the Covid-19 pandemic. This study used a descriptive-explatory and analytical approach. The data sources used are survey data, government policy circulars related to the Covid-19 pandemic and character-related laws and regulations. Data analysis used content analysis and continued with drawing conclusions. The findings of this study reveal that among the forms of revitalization are institutionalizing a holistic and character-based learning model, moral, value, religion and citizenship education, synergy of family, school and community education, and revitalizing the role of social media and mass media.